Difa City Tour dan Pemenuhan Kebutuhan Wisata Difabel - Tuti Elfrida; Upik Dyah Eka Noviyanti (INKLUSI, 2019)
Various sectors seem to ignore the existence of persons with disabilities, including the tourism industry. The majority of tourist destinations have not provided accessible facilities for them. Transportation services also do not accommodate the mobility needs of persons with disabilities. This study focused on Ojek Difa in Yogyakarta. Through observation and interviews, qualitative data was obtained to see the recreational needs of persons with disabilities and how the roles of Ojek Difa. The study found that people with disabilities have different ways of defining tourism activities. Ojek Difa offers Difa City Tour to provide services for disabled people who want to take a tour in the city or visit other tourist destinations. The existence of Difa City Tour in the Ojek Difa organization shows the importance of involving service providers from groups of persons with disabilities in the tourism sector, especially in serving disabled tourists.[Berbagai sektor tampak mengabaikan keberadaan difabel, termasuk industri pariwisata. Mayoritas destinasi wisata belum menyediakan fasilitas yang aksesibel bagi difabel. Layanan transportasi juga kurang mengakomodasi kebutuhan mobilitas difabel. Penelitian ini terfokus pada Ojek Difa di Yogyakarta yang memberikan layanan mobilitas bagi para difabel. Melalui observasi dan wawancara, data kualitatif diperoleh untuk melihat kebutuhan wisata para difabel. Penelitian menemukan bahwa para difabel memiliki cara berbeda dalam mendefinisikan kegiatan wisata. Ojek Difa menawarkan Difa City Tour untuk menyediakan layanan bagi para difabel yang ingin melakukan tur dalam kota atau mengunjungi destinasi wisata lainnya. Eksistensi Difa City Tour dalam organisasi Ojek Difa menunjukkan pentingnya melibatkan pegawai atau penyedia layanan dari kelompok difabel di sektor pariwisata terutama dalam melayani para wisatawan difabel.]